Preparation and Characterization of Some New Azo Dyes and Study of their Stability and Bacterial and Laser Activity - Hatem Abdel Karim Ibrahim; Diana A. Shaker (American Journal of Bioscience and Clinical Integrity, 2025)
The research included the preparation of some azo dyes by reacting the diazonium salt prepared from the reaction of 5-methyl-1,3,4-thiadiazole-2-amine with hydrochloric acid and sodium nitrite and then reacting the salt with the coupling solution (beta-naphthol, alpha-naphthol, 4-hydroxy-3-methoxybenzaldehyde, 2-aminophenol, 4-chloroaniline). The structures of the prepared compounds were confirmed by physical and spectroscopic methods such as infrared spectrum and proton nuclear magnetic resonance spectrum (1H-NMR). The stability of the dye was tested by dyeing three pieces of cloth, wool and cotton, then washing them with soap and water and comparing them afterwards. The effectiveness of the bacterial dyes was tested against two types of Gram-positive and Gram-negative bacteria. Then some of the compounds were with a helium-neon laser for four periods, then the physical properties after that.